An assessment of data sources, data quality and changes in national forest monitoring capacities in the Global Forest Resources Assessment 2005-2020 - Nesha, M.K.; Herold, M.; Sy, Veronique de; Duchelle, Amy E.; Martius, C.; Branthomme, A.; Garzuglia, M.; Jonsson, O.; Pekkarinen, A. (IOP Publishing, 2021)
Globally, countries report forest information to the Food and Agriculture Organization of the United Nations (FAO) Global Forest Resources Assessments (FRA) at regular intervals. While the status and trends of national forest monitoring capacities have been previously assessed for the tropics, this has not been systematically done worldwide. In this paper, we assess the use and quality of forest monitoring data sources for national reporting to the FRA in 236 countries and territories. More specifically, we (1) analyze the use of Remote Sensing (RS) for forest area monitoring and the use of National Forest Inventory (NFI) for monitoring forest area, growing stock, biomass, carbon stock, and other attributes in FRA 2005-2020, (2) assess data quality in FRA 2020 using FAO Tier-based indicators, and (3) zoom in to investigate changes in tropical forest monitoring capacities in FRA 2010 - 2020. Globally, the number of countries monitoring forest area using RS at good to very good capacities increased from 55 in FRA 2005 to 99 in FRA 2020. Likewise, the number of countries with good to very good NFI capacities increased from 48 in FRA 2005 to 102 in FRA 2020. This corresponds to ~85% of the global forest area monitored with one or more nationally-produced up-to-date RS products or NFI in FRA 2020. For large proportions of global forests, the highest quality data was used in FRA 2020 for reporting on forest area (93%), growing stock (85% ), biomass (76%), and carbon pools (61%). Overall, capacity improvements are more widespread in the tropics, which can be linked to continued international investments for forest monitoring especially in the context of Reducing Emissions from Deforestation and Forest Degradation in tropical countries (REDD+). More than 50% of the tropical countries with targeted international support improved both RS and NFI capacities in the period 2010-2020 on top of those that already had persistent good to very good capabilities. There is also a link between improvements in national capacities and improved governance measured against Worldwide Governance Indicators (WGI). Our findings – the first global study – suggest an ever-improving data basis for national reporting on forest resources in the context of climate and development commitments, e.g. the Paris Agreement and Sustainable Development Goals.